Development of a chemically modified sensor for the voltammetricdetermination of carbofuran; Instrumental Methods of Analysis: Modern Trends and Applications (IMA-2021) - Barek J. Jiri; Solomonenko A. N. Anna Nikolaevna; Dorozhko E. V. Elena Vladimirovna; Korotkova E. I. Elena Ivanovna (2021, 2021)
Title screen